VOICES FROM STEPHANIK'S HOLIDAY - Savchuk, R. L. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
"Voice from Rusov" is such an apt metaphorical name for the book of stories and interviews with participants of the St. Stephen's Day, which took place in the writer's estate on the occasion of his 150th anniversary. It would seem that a lot of time has passed since then, however, reading this edition now, we can see almost all the events of the unforgettable event, which gathered a large crowd of guests from Ukraine and abroad in May 2021. No, this book is not a chronology of the unfolding of the festive celebrations in Rusov, it is rather intended to convey the unforgettable and amazing atmosphere in which both Stefanyk's speech and the words of the numerous participants of the event and the citizens of Rusov themselves, who came to bow and pay their respects to the outstanding novelist Vasyl Stefanik.